Can Gender Quotas in Candidate Lists Empower Women? Evidence from a Regression Discontinuity Design - Manuel F. Bagues; Pamela Campa (Institute of Labor Economics (IZA), 2017)
We provide a comprehensive analysis of the short- and medium-term effects of gender quotas in candidate lists using evidence from Spain, where quotas were introduced in 2007 in municipalities with more than 5,000 inhabitants, and were extended in 2011 to municipalities with more than 3,000 inhabitants. Using a Regression Discontinuity Design, we find that quotas raise the share of women among council members but they do not affect the quality of politicians, as measured by their education attainment and by the number of votes obtained. Moreover, within three rounds of elections, women fail to reach powerful positions such as party leader or mayor, and we do not observe any statistically or economically significant changes in the size and composition of public finances.
Keywords: D72; H72; J16; 330; gender quotas in candidate lists; regression discontinuity design